On some nonlocal problems in the calculus of variations. (April 2022) - Chipot, Michel; Mikayelyan, Hayk
Abstract: The goal of this paper is to investigate some nonlocal problems of the calculus of variations where pointwise comparisons principles fail but where some kind of nonlocal maximum principle or monotonicity property remains true for some quantities attached to the problem. A special attention will be given to a nonlocal energy recently introduced in Mikayelyan (2018).